Modern Gothic and the House of God: Revivalism and Monasticism in Two Twentieth-Century Anglican Chapels. (2nd April 2016) - Lepine, Ayla
Abstract : In the early twentieth century, British architects increasingly turned away from the Gothic Revival towards new forms of architectural expression. However, in many key contexts and projects this style continued to evolve. Two architects, John Ninian Comper (1864–1960) and Temple Lushington Moore (1856–1920), were especially invested in medievalism and, more broadly, in the richness of architectural revivalism. Both worked in different ways within this set of practices in order to demonstrate revivalism's wide appeal for modern culture, and for sacred spaces in particular. This article compares two Church of England chapels that have received very little art historical attention, but which are linked in a series of ways. Moore's chapel for Pusey House in Oxford was completed in 1914, with additions by Comper in the 1930s. The chapel for the Anglican convent at London Colney in Hertfordshire, established by All Saints Sisters of the Poor, was designed by Comper in the 1920s and extended by his son Sebastian Comper in the 1960s. In both cases, historicism and revivalism in architecture and design heralded not a conservative return to previous generations' experiences of religion and of Anglicanism in particular, but a new way forward in liturgical ritual, social cohesion, and multisensory experiences of the sacred. In both cases, I argue, the connection between the visual cultural legacies of High Anglicanism following the Oxford Movement in the nineteenth century, and the unique characteristics of small-scale intimate worship in the all-male context of Pusey House and all-female context of London Colney, created new and intensive zones for revivalist monasticism that were as medievalist as they were modern.